PENERAPAN MODEL THINK-PAIR-SHARE BERBANTUAN LEMBAR KERJA PESERTA DIDIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X MA PROYEK UNIVA MEDAN - Lubis, Anggi Rizki Ananda Putri (Journal of Innovative and Creativity, 2026)
The main problem in this study is that the mathematics learning outcomes of students, especially in the X-3 class of Private MA UNIVA Medan, are still low. This study aims to improve students' mathematics learning outcomes using the Think-Pair-Share (TPS) learning model assisted by Student Worksheets (LKPD) for students in grades X-3 of Private MA UNIVA Medan. The research uses a type of class action research (Class Acion Research) which consists of two cycles where each cycle is carried out 4 meetings with a sample of 30 students. The instruments used included learning outcome tests, observation sheets, and student response questionnaires. The data analysis technique uses quantitative and qualitative analysis. The results achieved in this study are: (1) in the first cycle, the average score of learning outcomes of students in class X-3 of the Private MA Medan Project was 71.46 while in the second cycle, the average score of learning outcomes was obtained which was higher, namely 80. Students' mathematics learning completeness has also increased. In the first cycle, as many as 14 (47%) students achieved learning completion, while in the second cycle as many as 29 (97%) students achieved learning completeness and classical completeness was achieved, (2) there was an increase in student learning activities in each cycle. This means that the completeness of learning in cycle II was achieved classically because the number of students who completed reached more than 80%. Based on the results of the research mentioned above, it can be concluded that the results of mathematics learning through the Think-Pair-Share type cooperative model of students in class X-3 of the Private MA Univa Project have increased.